Familial deep endometriosis: A rare monogenic disease?. (February 2018) - Isidor, Bertrand; Latypova, Xenia; Ploteau, Stéphane
Abstract: Endometriosis is a frequent cause of pelvic pain and subfertility in women of reproductive age. Presence of extra‐uterine endometrial-like tissue is responsible for non-specific symptoms such as chronic pelvic pain, dysmenorrhea, dyspareunia, dyschesia and sometimes infertility. Three different phenotypes according to the location of the lesions are described, namely peritoneal, ovarian and deep infiltrating endometriosis. Deep endometriosis is considered as a distinct homogeneous disease. Heritability of endometriosis has been previously demonstrated. Despite extensive efforts to characterize candidate alleles contributing to genetic basis of endometriosis, these factors relevant to endometriosis pathophysiology remain unclear. No high penetrance pathogenic variant could be identified. We report herein two families with familial aggregation of severe deep infiltrating endometriosis, providing further evidence for monogenic mendelian inheritance of this form of endometriosis.